Sensitivity analysis of pre-stressed concrete sleepers for longitudinal crack prorogation effective factors. (August 2016) - Rezaie, F.; Bayat A., M.; Farnam, S.M.
Abstract: B70 mono-block pre-stressed concrete sleepers are one of the most common sleepers in Iran's railways industry. They have been used in many of the country's railway transition lines. The B70 types of sleepers are classified as pre-stressed concrete beams; therefore the value of pre-stressing force is one of the most important parameters in the field of sleepers' structural designing. Selecting high pre-stressing force due to the fact that it increases the steel bars strength, could increase the possibility of longitudinal cracks formation before service loading, especially if the tensile strength is low. Therefore, pre-stressing force and tensile strength are two important factors for investigating the sensitivity of longitudinal crack formation and propagation in sleepers. Sensitivity analysis has been conducted for tensile strength of concrete and the pre-stressing force in the steel bars, by using finite element method. It could be clearly seen in the results that increasing the tensile strength of concrete, increases the cross section capacity. This increase in the capacity does not have a direct relationship with the increase of the tensile strength. Also the numerical model indicates a linear behavior between different pre-stressing forces and maximum tensile stress around the dowels. Applying higher pre-stressing force values can increase the possibility of longitudinal cracks prior to service loading of the sleepers and also long-term sleepers' service life. Highlights: Longitudinal crack formation in pre-stressed concrete B70 sleeper before service load is studied with numerical analysis. The effect of presence of sand and also water freezing within the dowels is studied. The abovementioned items are modeled as a linear load distribution along the height of dowels for B70 sleeper. Sensitivity analysis of the model for the changes of pre-stressing force and tensile strength are studied.